2005
DOI: 10.1523/jneurosci.4925-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Changes in Glucose Differentially Modulate the Excitability of Hypothalamic Melanin-Concentrating Hormone and Orexin NeuronsIn Situ

Abstract: The physiological signaling mechanisms that link normal variations in body energy status to the activity of arousal-and metabolismregulating brain centers are not well understood. The melanin-concentrating hormone (MCH) and orexin/hypocretin types of neurons of the lateral hypothalamus (LH) exert opposing effects on arousal and metabolism. We examined whether shifts in brain extracellular glucose that correspond to physiological changes in blood glucose can alter the electrical output of neurochemically and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
296
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(323 citation statements)
references
References 32 publications
25
296
1
1
Order By: Relevance
“…1 A, n ϭ 15 cells). This electrical fingerprint was previously described for orexin neurons (21,22). In contrast, adapting orexin cells exhibited a strikingly different type of rebound potential: a transient depolarization crowned with spikes; we called this new type of orexin cell fingerprint ''Type-D'' (Fig.…”
Section: Transient and Sustained Glucose Sensors Among Orexin Neuronsmentioning
confidence: 56%
See 2 more Smart Citations
“…1 A, n ϭ 15 cells). This electrical fingerprint was previously described for orexin neurons (21,22). In contrast, adapting orexin cells exhibited a strikingly different type of rebound potential: a transient depolarization crowned with spikes; we called this new type of orexin cell fingerprint ''Type-D'' (Fig.…”
Section: Transient and Sustained Glucose Sensors Among Orexin Neuronsmentioning
confidence: 56%
“…6 A and B), cells were injected every 20 -40 s with a fixed-amplitude (10 -40 pA, 1-s duration) square pulse of hyperpolarizing current (22). The amplitude of the resulting downward deflections in membrane potential is proportional to membrane resistance (Ohm's law).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…OX neuron activation is to be expected in this model due to at least two mechanisms. First, in vitro electrophysiological studies indicate that OX cells are directly stimulated by low glucose [28]. Second, activation of corticotrophin-releasing factor (CRF) neurons in response to stressors such as restraint and footshock is implicated in producing behavioral activation and Fos expression in OX neurons [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Orexin neurons are localised in the posterolateral hypothalamus and project into the entire brain except the cerebellum [1]. Electrophysiological studies on hypothalamic slices have shown that orexin neurons are responsive to peripheral metabolic cues [4,5]. The excitability of orexin neurons was inhibited by glucose and leptin, indicators of high energy levels, whereas ghrelin, a signal for energy depletion, caused a stimulatory effect.…”
mentioning
confidence: 99%